Trends in Incidence and Mortality of Stroke in China From 1990 to 2019 - Sun, Tong; Chen, Siyang; Wu, Ke; Sun, Min; Zhang, Xianyan; You, Chao (Frontiers in Neurology, 2021)
Objective: Stroke is a leading cause of mortality and morbidity globally. This study aims to analyze the burden and 30-year trends of ischemic stroke, intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH) in China. Methods: Data including incidence and mortality of stroke in China from January 1, 1990, to December 31, 2019 were derived from the Global Burden of Disease (GBD) study 2019. The absolute numbers of incident cases and deaths over the time, and age-standardized rates per 100,000 including age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) were analyzed. Results: In 2019, there were 3.9 (95% UI 3.4-4.5) million incident cases and 2.1 (3.4-4.5) million deaths related to stroke in China. The ASIR and ASMR of stroke in China was 200 (176-230) and 127 (110-144). From 1990 to 2019, the ASIR of ischemic stroke had increased by 35.0% (29.0 to 40.0) while the ASIR of ICH and SAH had decreased by –53.0% (–56.0 to –50.0) and by –39.0% (–44.0 to –35.0), respectively. The ASMR of ischemic stroke had increased by 3.0% (–26.0 to 16.0) while the ASMR of ICH and SAH had decreased by –48.0% (–59.0 to –38.0) and by –84.0% (–89.0 to –69.0), respectively. Conclusion: Although the incidence and mortality rates of stroke in China had decreased from 1990 to 2019, the number of incident cases and deaths nearly doubled. A sharp increase in incidence rate of ischemic stroke was observed. A higher incidence rate of ischemic stroke in females was also observed.